STUDY ON THE STAGE OF DEVELOPMENT AND VALUATION OF THE TOURIST POTENTIAL IN THE DANUBE DELTA AREA, ROMANIA - Jenica CĂLINA; Aurel CĂLINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current stage of development and capitalization of the tourist potential in the Danube Delta area was identified based on multidisciplinary research, presented in this paper, in which three stages were completed, which aimed at the study of the natural and anthropic tourist potential, as well as the circulation and activity touristic. Regarding the natural potential, it was found that it is very rich, diversified and valuable, showing a strong character of uniqueness and authenticity, through the multitude of endemic and protected plant and animal species, many of which are included in the UNESCO international heritage. Although the cultural-historical and monumental heritage is not very rich, compared to other areas in the country, it represents a strong asset for attracting tourists due to the age and date of attestation of the existing historical fortresses and monuments. The current stage of development of tourism capacities was highlighted through the analysis of several indicators that focused primarily on the development of tourist activity in the villages of this region and through their comparative analysis with the values recorded at the national level. A comparative assessment of the flow of Romanian and foreign tourists arriving in the period 2018-2022, in this area, was also carried out, in order to highlight the level of capitalization of the existing tourist capacities and the stage of its promotion, at the national and international level.